Globalisation, Neoliberalism, and the Reform of Teacher Education in England - Furlong, J (2013)
Over the last 30 years, teacher education has become a major area of government policy in many countries around the world. One of the key factors driving this change has been the growing significance of globalisation, "imagined" by most countries as necessitating the pursuit of neoliberal policies. But neoliberalism itself is not static; interpretations vary between different countries and change over time as a result of political processes. This article takes the case of England, focusing in particular on ways in which neoliberal teacher education policies changed and developed during the new Labour administration (from 1997-2010) and are changing again under the present Coalition government. Both administrations have been fundamentally committed to the pursuit of neoliberal policies, but their interpretations of neoliberalism have varied significantly; as a result, their policies on teacher education are also very different. Despite the very real material changes brought about by globalisation, the article concludes by emphasising the significance of national politics in the development of teacher educational policy. © 2013 Copyright Taylor and Francis Group, LLC.